HUBUNGAN STATUS GIZI DENGAN HASIL BELAJAR PENJASORKES SMK LABOR PEKANBARU - Muhammad Azizan Shah; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study is based on the fact that the quality of students' learning outcomes penjasorkes still low. This is evident from the results of the first semester exam is still below average or below the passing standard that many students do remedial on subjects such penjasorkes that failed, so students take the exam again to improve that value. Many factors mempegaruhi sisiwa low learning outcomes, one of which is visible on the nutritional status of students. The aim in this study was to determine the relationship of nutritional status and vocational learning outcomes penjasorkes Labor pekanbaru. The population in this study were all students of SMK Labor Accounting classes totaling 10 157 people. Sampling technique with purposive sampling, the sample in this study defined as 56 people. To get the research data used Anthropometrics test weight and height, and learning outcomes. Data were analyzed with product moment correlation. Based on the results of research that has been described in the previous chapter, it can be concluded that the results of the calculation of the correlation between nutritional status (X) with the learning outcomes penjasorkes (Y) obtained rhitung = 0.317 while rtabel at significance level α = 0:05 is 0.266. Means in this case there is a relationship between nutritional status (X) with the learning outcomes penjasorkes (Y), given that both the nutritional status of the students, the better the learning outcomes obtained.Keywords: Nutritional Status, Learning Outcomes